Ancistrosyllis matlaensis n. sp. (Polychaeta: Pilargidae) from the Sundarban Estuarine System, India - Mandal, Sumit; Deb, Soumya (Zootaxa, 2018)
A new species of family Pilargidae, Ancistrosyllis matlaensis n. sp. is described from the Sundarban Estuarine System, India. The new species can be distinguished from its congeners by a combination of characters: absence of median antenna and eyes, shape of tentacular and dorsal cirri, structure of notopodia and neuropodia, and first appearance of notopodial hooks. The new species closely resembles Ancistrosyllis falcata.